Common Ground or Double Bind? The Possibility of Dialogue in Plato’s Crito - Feldman, Sarah (Pontificia Universidad Católica del Perú. Departamento de Humanidades, 2022)
Much recent scholarship on Plato’ Crito has revolved around the controversy about the relationship and possible compatibility between the arguments Socrates gives in his own person (SocratesS) and those he gives in the person of the Laws (SocratesL). By contrast, the relation between the arguments given by SocratesL and those given by Crito continues to be seen as uncontroversial: by the end of the dialogue, commentators agree, Crito has no choice but to concede to the force of SocratesL’s arguments. Against this traditional reading, this paper will argue not only that SocratesL’s arguments fail to secure Crito’s agreement, but also that two characters’ attempts to communicate end at an impasse that seems to leave little room for meaningful shared discourse –and may even undermine Crito’s belief in the possibility of meaningful speech. My interpretation is informed by Socrates’ account (at 49c9-e3) of the need for and nature of a “common ground” as a requisite for genuine dialogue. This passage, I argue, challenges the traditional analysis of Crito as the representative of a particular value system or a particular “type”, demanding, instead, a consideration of the effect of Socrates’ arguments upon Crito in light of a more robust view of the latter’s perspective. Such a reconsideration has consequences not only for our appreciation of the dramatic structure of the dialogue, but also for how we understand one of the dialogue’s central, if underexplored, themes: the belief in a shared logos and the psychagogic necessity and perils of testing that belief.

Gran parte de los estudios recientes sobre el Critón de Platón han girado en torno a la controversia sobre la relación y posible compatibilidad entre los argumentos que plantea Sócrates a nombre propio (SócratesS) y aquellos que ofrece en nombre de las Leyes (SócratesL). Por el contrario, la relación entre los argumentos de SócratesL y aquellos planteados por Critón no produce, incluso hoy, controversia alguna: los comentaristas están de acuerdo en que al final del diálogo Critón no tiene más remedio que ceder ante la fuerza de los argumentos de SócratesL. En contra de esta lectura tradicional, en este artículo se argumentará no solo que los argumentos de SócratesL fracasan a la hora de garantizar un acuerdo con Critón, sino también que la búsqueda de comunicación por parte de ambos personajes termina en un callejón sin salida que parece dejar poco espacio para un discurso compartido con sentido –e incluso puede socavar la confianza de Critón en la posibilidad de un lenguaje significativo. Mi interpretación se construye a partir de la posición de Sócrates (en 49c9-e3) respecto de la necesidad y la naturaleza de un “suelo común” como un requisito para el diálogo genuino. Este pasaje, sostengo, desafía el análisis tradicional de Critón como un representante de un sistema de valores particulares o un “tipo” particular, exigiendo, en cambio, considerar el efecto de los argumentos de Sócrates en Critón a la luz de una visión más sólida de la perspectiva de este último. Tal reconsideración tiene consecuencias no solo para nuestra comprensión de la estructura dramática del diálogo, sino también para la forma en que entendemos uno de sus temas centrales, aunque poco explorados: la confianza en un logos compartido así como la necesidad y los peligros psicagógicos de someter a prueba dicha confianza.
Keywords: Crito; Pre-conditions of dialogue; Agreement; Perspective; Critón; Pre-condiciones de diálogo; Acuerdo; Perspectiva; https://purl.org/pe-repo/ocde/ford#6.03.01